(3GdCQHYhf MOjKG Yf CQHYjf TjNG ef CQHYjf eOjfI aj CQHYjf HGHGs - (3CHh GdbGSe Ydj Hf GdMSjf Hf YHO Gddg Hf GdMSjf GdTGaYjs ((3CMeO YGQa MceJ Hf EHQGgje Hf YUeJ GdMSjfj , J (B1275 (3g`s)
(3ChdgG (B:s
(3GdMeO ddg GdbGOQ GdbGgQ Gdbhj aEf Gddg SHMGfg Ndb Ndbg ef GdWjf hCfTCge HbOQJg adeG hba YdeGDge Ydi eG MVge fHjge Ydjg HGOQ HYVge Edi GeJKGd eG fOHge Edjg hUfa LeGYI efge CQHYjfjGJ SeYJ efge hGTJgQJ Hge hfbdJ Yfge hGNJda ebGUOge aj JUfjagG hde jJabhG Ydi s
(3BNQgG (B:s
(3bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd aj BNQ UdGJg Ch Mjf jfUQa (B" (3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf (B" (3gPG MOjK ZQjH ef MOjK CHj SYjO SYO Hf eGdc Hf SfGf gPG BNQ GdCQHYjfs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3TgGOGJ GdQhGjI (B: s
(3GdELGRGJ h GdSeGYGJ (B:s
Keywords: (3GdMOjK hGdeUWdMs